2019
DOI: 10.1017/s1463423619000343
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of the Turkish version of the WHO-5, in adults and older adults for its use in primary care settings

Abstract: Background: This study aims to determine the psychometric properties of the World Health Organization Well-Being Index (WHO-5) Turkish version in Turkish adults and older adults. Methods: This is a multicenter cultural adaptation study carried out with 1752 participants. Internal consistency (by Cronbach’s alpha); Construct validity (by known groups and confirmatory factor analysis-CFI) and discriminant validity are evaluated stratified by adults and older adults. Cohen’s Effect Size is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 41 publications
8
28
0
Order By: Relevance
“…As a result of the reliability analysis applied to the well-being scale, the total Cronbach's Alpha reliability coefficient of the scale was found to be 0.877. The results of factor analysis applied to the well-being scale showed that the scale in this study exhibited a single-factor structure similar to the study by Eser et al (2019). As a result of the analysis, it was seen that this single-factor structure explained 69.960% of the total variance, and the scale was included in the analyzes as a single-factor (KMO = 0.869, χ 2 = 8980.532, df = 10, p < .001).…”
Section: Validity and Reliability Analysessupporting
confidence: 80%
See 1 more Smart Citation
“…As a result of the reliability analysis applied to the well-being scale, the total Cronbach's Alpha reliability coefficient of the scale was found to be 0.877. The results of factor analysis applied to the well-being scale showed that the scale in this study exhibited a single-factor structure similar to the study by Eser et al (2019). As a result of the analysis, it was seen that this single-factor structure explained 69.960% of the total variance, and the scale was included in the analyzes as a single-factor (KMO = 0.869, χ 2 = 8980.532, df = 10, p < .001).…”
Section: Validity and Reliability Analysessupporting
confidence: 80%
“…"World Health Organization Well-Being Index (WHO-5)," which was developed by Bech, Gudex, and Staehr Johansen (1996), revised by WHO (1998) and whose Turkish adaptation was examined by Eser et al (2019) in terms of validity and reliability, was used to evaluate the states of the well-being of the participants. This scale, which is widely and internationally used to measure the well-being of the participants (Topp, Ostergaard, Sondergaard, & Bech, 2014), consists of one dimension and each item is scored with a 6-point Likert scale ranging from "at no time (0)" to "all of the time (5)."…”
Section: Data Collection Toolsmentioning
confidence: 99%
“…Summing all items can give a total score ranging from 0 to 25, with high scores referring to an increased well-being. Satisfactory psychometric properties of the scale were reported in Turkish language (Eser et al, 2019 ). In this study, the Cronbach’s alpha coefficient of WHO-5 was 0.88.…”
Section: Methodsmentioning
confidence: 99%
“…The WHO-5 includes five items rated on a 6-point Likert scale response format that ranges from 0 = not present to 5 = constantly present. The scale was translated into Turkish Eser et al ( 2019 ).…”
Section: Methodsmentioning
confidence: 99%